North Korea’s nuclear use scenario - Jangho Park; Jisoo Park (선진국방연구, 2022)
This paper analyzes the most challenging nuclear use scenario while leaving all possibilities open to using nuclear weapons and verifying North Korea’s possibility of using nuclear weapons. Until now, research on North Korea’s nuclear use scenario has been academically unsystematic, has lacked empirical examples, included cynical attitudes toward nuclear weapons, and has been based on analytical techniques containing limitations. Accordingly, this paper intends to suggest strategic implications for the existing North Korean nuclear threat by presenting the most challenging nuclear use scenario, which has not been covered in previous studies, using the “Nuclear War Potential Model” and “Impact-Uncertainty Grid.”